Mídia e beleza negra: a mulher negra em propagandas televisivas de produtos de higiene e beleza - Gomes, Ana Paula Pereira (2007)
This research addresses the representation of black women in television advertisements of hygiene and beauty products in Brazil in the early 2000s. The analysis sought to investigate the historical and sociological context of the emergence of Rexona Ebony, Vasenol (for "dark and black skin") and Seda for curly hair "chemically treated" and its advertisements. Given that they are products belonging to the multinational Unilever and that already existed in other versions, the dissertation sought to analyze which political and social factors influenced the market choice of brands in launching variations aimed at the black skin public at this specific moment, as well as to analyze how this phenomenon dialogues with the concept of black beauty; and how the media representation elaborated by these brands impacts the self-image of their consumers.